2019
DOI: 10.1186/s10020-019-0096-z
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin induced oxidative stress attenuation by N-acetylcysteine co-treatment: a fibroblast and epithelial cell in-vitro study in idiopathic pulmonary fibrosis

Abstract: Background Idiopathic Pulmonary Fibrosis (IPF) is a fatal lung disease of unknown etiology with only two federally approved drug options. Given the complex molecular pathogenesis of IPF involving multiple cell types and multiple pathways, we explore the effects of a potential antifibrotic and antioxidant drug combination. Curcumin is a polyphenolic compound derived from turmeric with significant biological activity including a potential antifibrotic capacity. N-acetylcysteine (NAC) is a precursor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 42 publications
0
15
0
Order By: Relevance
“…In addition to proliferation inhibition, curcumin also inhibited TGF-β-dependent myofibroblast differentiation via inhibition of TGF-β-induced phosphorylation of Smad2/3 and ERK1/2, as well as inhibited collagen secretion from IPF fibroblasts [ 33 ]. Another study showed that curcumin inhibited the activation of genes associated with myofibroblast activation and proliferation, inhibited migration, induced apoptosis, and induced oxidative stress in pulmonary fibroblasts [ 50 ]. The antifibrotic effects of curcumin in pulmonary fibroblasts were also attributed to overexpression of cathepsins K and L [ 51 ], whereas another study showed that curcumin inhibited TGF-β1-dependent myofibroblast differentiation of pulmonary fibroblasts via peroxisome proliferator-activated receptor γ (PPARγ)-driven upregulation of cathepsins B and L [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to proliferation inhibition, curcumin also inhibited TGF-β-dependent myofibroblast differentiation via inhibition of TGF-β-induced phosphorylation of Smad2/3 and ERK1/2, as well as inhibited collagen secretion from IPF fibroblasts [ 33 ]. Another study showed that curcumin inhibited the activation of genes associated with myofibroblast activation and proliferation, inhibited migration, induced apoptosis, and induced oxidative stress in pulmonary fibroblasts [ 50 ]. The antifibrotic effects of curcumin in pulmonary fibroblasts were also attributed to overexpression of cathepsins K and L [ 51 ], whereas another study showed that curcumin inhibited TGF-β1-dependent myofibroblast differentiation of pulmonary fibroblasts via peroxisome proliferator-activated receptor γ (PPARγ)-driven upregulation of cathepsins B and L [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Single herbs used in IPF treatment are shown in Table 2 [ [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] ]. Under the guidance of the theory of TCM, compound preparations and single TCM act on all aspects of lung disease treatment through multiple channels and multiple targets, especially show the unique advantages in the treatment of IPF.…”
Section: Compound Prescriptions Of Tcm and Single Tcm In The Ipf Treamentioning
confidence: 99%
“… [ 54 ] Curcuma longa L. It can inhibit type I collagen synthesis and deposition, and TGF-β1 expression. [ 55 ] Salvia miltiorrhiza Bunge It can inhibit Smad-dependent signalling and Smad-dependent MAPK pathway, and restore the balance of Nrf2-NOX4. [ 56 ] Angelica sinensis (Oliv.)…”
Section: Compound Prescriptions Of Tcm and Single Tcm In The Ipf Treamentioning
confidence: 99%
“…The 1 H NMR spectrum of EANA has been previously reported [16] and shows that plumbagin is the major bioactive component. N-acetylcysteine (NAC) (Sigma-Aldrich; St. Louis, MO, USA) was selected to be a oxidative stress scavenger for validating the influence of oxidative stress [17][18][19] by 1 h pretreatment of 10 mM [20].…”
Section: Crude Extracts and Chemicalmentioning
confidence: 99%